Perencanaan Bangunan Pelindung Pantai di Kawasan Pantai Pesaren Belinyu Provinsi Kepulauan Bangka Belitung - Atiqoh Dwi Lestari; Endang Setyawati Hisyam; Indra Gunawan (Universitas Islam 45, 2022)
Pesaren beach is one of the beaches in Bintet Village, Belinyu District, Bangka Belitung Islands Province, where this beach has been functioned as a tourist area as well as a boat port for fishermen. A frequent problem in Pesaren beach is the abrasion that causes damage to local infrastructure; hence, a coastal protection plan is needed to prevent further losses. This research aims to find out the pattern of currents and sediments using the auxiliary applications, as well as to determine and plan the type of coastal protective building that is appropriate with the Pesaren beach conditions. Based on planning analysis, the dominant cause of abrasion is large waves from the north, as well as other factors, i.e., the direction of currents and sediments dominant that perpendicular to the coast; therefore, the type and shape of selected coastal protective buildings were proposed with the following specifications: breakwater with a height (HT) of 5.2 m, peak width (lp) of 1.5 m, total base width (b) of 26.7 m, breakwater (ly) length of 350 m, protection layer width (t) of 1 m, number of stones per 10 m² (N) of 86 grains, weight of main layer stone grains (W) of 0.179 tons, weight of second-tier stone grains (W/10) of 0.0179 tons, weight of stone grains at the core of the structure (W/200) of 0.000895 tons, and weight of breakwater foot grains (W/15) of 0.0119 tons.